2020
DOI: 10.3390/life10090197
|View full text |Cite
|
Sign up to set email alerts
|

From Bench to Bedside in Tongue Muscle Cancer Invasion and Back again: Gross Anatomy, Microanatomy, Surgical Treatments and Basic Research

Abstract: Tongue squamous cell carcinoma is the most common malignancy in the oral cavity. Despite advances in diagnosis and treatment, the prognosis of advanced states has not significantly improved. Depth of invasion, pattern of invasion such as tumor budding grade, lingual lymph node metastasis in early stages, collective cell migration and circulating tumor cells in peripheral blood are some examples of the mechanisms that are currently receiving increasing attention in the evaluation of the prognosis of tongue canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…21 Another hypothesis that could explain the worse prognosis for posterior tumors is the easier access to a wide spectrum of local pathways of spread (ie, styloglossus, genioglossus and hyoglossus, main branches of lingual and hypoglossal nerves). 22 It has been postulated that a more complex geometry of growth pattern could increase the difficulty of achieving adequate resection margins in posterior tumors. 23 Indeed, the results shown herein do not support this conclusion, as we found no relevant differences in terms of margin status between anterior and posterior tumors (eFigure 3 in Supplement 1).…”
Section: Discussionmentioning
confidence: 99%
“…21 Another hypothesis that could explain the worse prognosis for posterior tumors is the easier access to a wide spectrum of local pathways of spread (ie, styloglossus, genioglossus and hyoglossus, main branches of lingual and hypoglossal nerves). 22 It has been postulated that a more complex geometry of growth pattern could increase the difficulty of achieving adequate resection margins in posterior tumors. 23 Indeed, the results shown herein do not support this conclusion, as we found no relevant differences in terms of margin status between anterior and posterior tumors (eFigure 3 in Supplement 1).…”
Section: Discussionmentioning
confidence: 99%
“…The optimal surgical margin of conventional OSCC has been considered to be 5 mm 9 , 10 , but this designation is controversial 11 - 14 . However, because tongue muscle invasion impact on tumor progression and has a relatively poor TSCC prognosis, and the optimal surgical margin of TSCC is still controversial and values have been proposed, including tongue compartment surgery 3 , 12 - 16 . Zanoni et al 12 suggested 0.22 cm as the optimal surgical margin for the TSCC cases, where the proportion of T 1 and T 2 stages reached 87%.…”
Section: Discussionmentioning
confidence: 99%
“…The tongue, unlike other tissues in the oral cavity, has a characteristic structure including a high content of muscle bundles and a rich lymphatic chain 2 . A high proportion of muscles in the tongue make so that it can be a routes for tumoral spread through muscle fibers, thus local recurrence could be higher with muscle invasion 3 . In addition to creating a specific tumor microenvironment, it can also induce lots of shrinkage at resection which is affected by tissue composition and tumor cells cohesiveness.(Fig.…”
Section: Introductionmentioning
confidence: 99%
“…TSCC is the most common malignancy in the oral cavity; despite advances in diagnosis and treatment, the prognosis of advanced states has not significantly improved [28]. The reported 5-year rates of diseasefree survival ranged from 30% to 72% for the younger cohorts (≤45 years ) and 42% to 81% for the older cohorts [29], and the etiology of tongue cancer, especially the molecular mechanism, remains unclear.…”
Section: Discussionmentioning
confidence: 99%